New species and records of Elachistinae (Lepidoptera: Gelechioidea, Elachistidae) from Nepal - Sruoga, Virginijus (Zootaxa, 2022)
Six species of Elachistinae are newly reported from Nepal, four of which are described as new: Elachista conspecta sp. nov., E. marginata sp. nov., E. minor sp. nov. and E. simulans sp. nov.                The new species are diagnosed and illustrated with photographs of the adults and genitalia. E. siamensis Sruoga & Kaila, 2019 and E. kurokoi Parenti, 1983 are recorded for the first time in Nepal.